Storm runners - Smith, Roland, 1951- (Scholastic Press, 2011)
Twelve-year-old Chase Masters travels the country with his father, a "storm runner," but he is tested in ways he never could have imagined when he and a new friend are caught in a hurricane near St. Petersburg, Florida.